2008
DOI: 10.1002/hyp.7094
|View full text |Cite
|
Sign up to set email alerts
|

Winter rain on snow and its association with air temperature in northern Eurasia

Abstract: Abstract:This study examines the characteristics of winter (Dec-Feb) rain-on-snow events and their relationship to surface air temperatures to reveal potential changes in rain-on-snow days under a warming climate over northern Eurasia. We found that rain-on-snow events mostly occur over European Russia during winter. Rain-on-snow days increase as air temperature increases and are primarily attributable to the increase in rainfall days. Air temperature is the primary cause for these changes, while the North Atl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
92
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 36 publications
7
92
0
Order By: Relevance
“…Ye et al (2008) observed an increase in RoS days in northern Eurasia, which they were able to correlate with the observed increase in air temperature and rainfall in the wintertime. Sui and Koehler (2001) attributed an increase in peak flows in the northern Danube tributaries in Germany to an increase in RoS events, based on the combination of decreasing SWE and increasing maximum daily winter precipitation sums they found at a number of climate stations in the area.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Ye et al (2008) observed an increase in RoS days in northern Eurasia, which they were able to correlate with the observed increase in air temperature and rainfall in the wintertime. Sui and Koehler (2001) attributed an increase in peak flows in the northern Danube tributaries in Germany to an increase in RoS events, based on the combination of decreasing SWE and increasing maximum daily winter precipitation sums they found at a number of climate stations in the area.…”
Section: Introductionsupporting
confidence: 61%
“…McCabe et al (2007) and Surfleet and Tullos (2013) defined an event as RoS-driven if simultaneously rainfall occurs, maximum daily temperature is greater than 0 • C, and a decrease in snowpack can be observed; while for Ye et al (2008), a RoS event takes place only when at least one of four daily precipitation measurements is liquid and the ground is covered by ≥ 1 cm of snow. Sui and Koehler (2001) found that most RoS events in southern Germany occurred when snowmelt was larger than the rainfall depth.…”
Section: Introductionmentioning
confidence: 99%
“…Winters with higher maximum temperatures had more ROS events than cooler winters due to more rainfall occurrences, for the case of south-central Ontario, Canada, for the 1971-2001 period (Casson et al 2010). Similarly, an increase in winter ROS events with warmer air temperatures for the northern Eurasian high-latitude regions was reported for the 1936-1990 period (Ye et al 2008). These increased ROS frequency and associated snowmelt in winter could have direct influence on decreased spring snow water equivalent (SWE) and spring water storage and supply in snowmelt-dominated regions (Jeong et al 2016c).…”
Section: Introductionmentioning
confidence: 73%
“…Warmer air temperatures in future climate can decrease ROS frequency by reducing snowfall and days with snow cover on the ground in mid-latitude regions (McCabe et al 2007). However, an increase in ROS frequency, due to increasing rainfall days, can be expected in high-latitude and mountainous regions, where, despite the increase in temperatures, snow cover is present during most of the winter months as air temperatures are generally below freezing point for these regions (Ye et al 2008). Therefore, it is very important to evaluate how these events will evolve in a future warming climate at regional scale.…”
Section: Introductionmentioning
confidence: 99%
“…Such events are therefore sensitive to small changes in winter climate. The occurrence of winter month rain-on-snow events has been observed to increase with increased air temperature; the rate of increase ranged from 0.5 to 2.5 events per winter per°C and was greater at locations with low air temperature (Ye et al 2008). …”
Section: Snow Structure and Propertiesmentioning
confidence: 99%